2013
DOI: 10.1155/2013/351942
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Vitamin D Receptor Gene Polymorphisms and Migraine without Aura in an Iranian Population

Abstract: Background. Inflammation has a key role in migraine pathophysiology. Vitamin D is an effective anti-inflammatory agent. The aim of this study was to investigate the association between migraine and two vitamin D receptor (VDR) polymorphisms (TaqI and FokI) and also the relationship between VDR polymorphisms and headache severity. Methods. In this case-control study we assessed 103 patients with newly diagnosed migraine without aura and 100 healthy subjects. Patients filled headache impact test-6 (HIT-6) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
1
25
2
1
Order By: Relevance
“…The role of vitamin D in headaches remains unclear, mainly due to predominantly small studies with inconsistent findings89101112131415161718 and the lack of large randomized supplementation trials that would show benefit after improvement of vitamin D status with vitamin D supplementation23. Our study, being one of the largest studies that have investigated the issue, supports the view that vitamin D may be beneficial in headache prevention.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The role of vitamin D in headaches remains unclear, mainly due to predominantly small studies with inconsistent findings89101112131415161718 and the lack of large randomized supplementation trials that would show benefit after improvement of vitamin D status with vitamin D supplementation23. Our study, being one of the largest studies that have investigated the issue, supports the view that vitamin D may be beneficial in headache prevention.…”
Section: Discussionsupporting
confidence: 66%
“…However, there is little data regarding the association between vitamin D exposure and headache. In a small case-control study, vitamin D receptor polymorphisms were found to be more prevalent in migraine patients than in controls and be related to severity of headache8. In a cross-sectional study from Norway, non-smoking participants with migraine or non-migraine headache had lower serum 25(OH)D concentration9, whereas no difference was observed among smokers.…”
mentioning
confidence: 94%
“…The majority of past studies have not demonstrated any difference in the serum levels of vitamin D in patients with migraine as compared to controls, but one study did show certain vitamin D polymorphisms to be associated with migraine without aura . The largest study published to date found an increased prevalence of persons with “non‐migraine” headache in the lowest quartile of serum vitamin D levels as opposed to the highest quartile (OR 1.2; 95% CI: 1.04, 1.29) .…”
Section: Vitamin D and Dietmentioning
confidence: 99%
“…Several restriction fragment length polymorphisms (RFLP) have been reported for the VDR gene, including sites cleaved by BsmI, ApaI, TaqI and FokI. Recently there have been a number of studies reporting that VDR gene polymorphisms have connections with some diseases, such as cancer, diabetes and cardiovascular disease …”
Section: Introductıonmentioning
confidence: 99%